2011
DOI: 10.1039/c0dt00820f
|View full text |Cite
|
Sign up to set email alerts
|

trans-FeII(H)2(diphosphine)(diamine) complexes as alternative catalysts for the asymmetric hydrogenation of ketones? A DFT study

Abstract: New insights into the structural, electronic and catalytic properties of Fe complexes are provided by a density functional theory study of model as well as real [Fe(II)(H)(2)(diphosphine)(diamine)] systems. Calculations conducted using several different functionals on the trans- and cis-isomers of [Fe(II)(H)(2)(S-xylbinap)(S,S-dpen)] complexes show that, as with the [Ru(II)(H)(2)(diphosphine)(diamine)] complexes, the trans-[Fe(II)(H)(2)(diphosphine)(diamine)] complex is the more stable isomer. Analysis of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 48 publications
0
10
0
1
Order By: Relevance
“…Complex 80 b likely served as the active catalyst in the hydrogenation. The reaction was assumed to follow an outer‐sphere mechanistic pathway (Scheme ),48bd which is analogous to the [RuCl 2 (diphosphine)(diamine)]‐catalyzed ketone hydrogenation shown in Scheme . The NH group was thought to be involved in the hydrogenation via a six‐membered ring transition state 84 .…”
Section: Mnh Catalysismentioning
confidence: 99%
“…Complex 80 b likely served as the active catalyst in the hydrogenation. The reaction was assumed to follow an outer‐sphere mechanistic pathway (Scheme ),48bd which is analogous to the [RuCl 2 (diphosphine)(diamine)]‐catalyzed ketone hydrogenation shown in Scheme . The NH group was thought to be involved in the hydrogenation via a six‐membered ring transition state 84 .…”
Section: Mnh Catalysismentioning
confidence: 99%
“…Ruthenium catalysts are used in a number of asymmetric hydrogen transfer systems. For example, the most effective and efficient class of catalysts for the enantioselective hydrogenation of pro-chiral ketones to chiral alcohols are the ruthenium(II) diphosphine-diaminebased complexes developed by Noyori et al [18,19], and recent practical [20,21] and theoretical [22,23] work has suggested that related iron complexes may be viable alternatives. The dimeric ruthenium complex (Scheme 1), widely known as the Shvo catalyst [24][25][26][27][28][29][30][31], acts as a catalyst for hydrogen transfer reactions between alcohols and aldehydes/ ketones, a process resulting from the scission of the Shvo catalyst into saturated 18-electron and unsaturated 16-electron mononuclear fragments (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…DFT calculations on related complexes support the assumption that these complexes are acting as bifunctional catalysts. [12] It is also important to note that Morris and co-workers achieved for the first time an enantioselective hydrogenation, although the conversion and enantioselectivity were modest (40 % conversion, 27 % ee).…”
mentioning
confidence: 99%